Answer:
0.292371705 if A=17
0.258819045 if A=15
Step-by-step explanation:
What are all the other options i dont understand
Answer:
Step-by-step explanation:
Given that:
The differential equation; ![(x^2-4)^2y'' + (x + 2)y' + 7y = 0](https://tex.z-dn.net/?f=%28x%5E2-4%29%5E2y%27%27%20%2B%20%28x%20%2B%202%29y%27%20%2B%207y%20%3D%200)
The above equation can be better expressed as:
![y'' + \dfrac{(x+2)}{(x^2-4)^2} \ y'+ \dfrac{7}{(x^2- 4)^2} \ y=0](https://tex.z-dn.net/?f=y%27%27%20%2B%20%5Cdfrac%7B%28x%2B2%29%7D%7B%28x%5E2-4%29%5E2%7D%20%5C%20y%27%2B%20%5Cdfrac%7B7%7D%7B%28x%5E2-%204%29%5E2%7D%20%5C%20y%3D0)
The pattern of the normalized differential equation can be represented as:
y'' + p(x)y' + q(x) y = 0
This implies that:
![p(x) = \dfrac{(x+2)}{(x^2-4)^2} \](https://tex.z-dn.net/?f=p%28x%29%20%3D%20%5Cdfrac%7B%28x%2B2%29%7D%7B%28x%5E2-4%29%5E2%7D%20%5C)
![p(x) = \dfrac{(x+2)}{(x+2)^2 (x-2)^2} \](https://tex.z-dn.net/?f=p%28x%29%20%3D%20%5Cdfrac%7B%28x%2B2%29%7D%7B%28x%2B2%29%5E2%20%28x-2%29%5E2%7D%20%5C)
![p(x) = \dfrac{1}{(x+2)(x-2)^2}](https://tex.z-dn.net/?f=p%28x%29%20%3D%20%5Cdfrac%7B1%7D%7B%28x%2B2%29%28x-2%29%5E2%7D)
Also;
![q(x) = \dfrac{7}{(x^2-4)^2}](https://tex.z-dn.net/?f=q%28x%29%20%3D%20%5Cdfrac%7B7%7D%7B%28x%5E2-4%29%5E2%7D)
![q(x) = \dfrac{7}{(x+2)^2(x-2)^2}](https://tex.z-dn.net/?f=q%28x%29%20%3D%20%5Cdfrac%7B7%7D%7B%28x%2B2%29%5E2%28x-2%29%5E2%7D)
From p(x) and q(x); we will realize that the zeroes of (x+2)(x-2)² = ±2
When x = - 2
![\lim \limits_{x \to-2} (x+ 2) p(x) = \lim \limits_{x \to2} (x+ 2) \dfrac{1}{(x+2)(x-2)^2}](https://tex.z-dn.net/?f=%5Clim%20%5Climits_%7Bx%20%5Cto-2%7D%20%28x%2B%202%29%20p%28x%29%20%3D%20%20%5Clim%20%5Climits_%7Bx%20%5Cto2%7D%20%28x%2B%202%29%20%5Cdfrac%7B1%7D%7B%28x%2B2%29%28x-2%29%5E2%7D)
![\implies \lim \limits_{x \to2} \dfrac{1}{(x-2)^2}](https://tex.z-dn.net/?f=%5Cimplies%20%20%5Clim%20%5Climits_%7Bx%20%5Cto2%7D%20%20%5Cdfrac%7B1%7D%7B%28x-2%29%5E2%7D)
![\implies \dfrac{1}{16}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B1%7D%7B16%7D)
![\lim \limits_{x \to-2} (x+ 2)^2 q(x) = \lim \limits_{x \to2} (x+ 2)^2 \dfrac{7}{(x+2)^2(x-2)^2}](https://tex.z-dn.net/?f=%5Clim%20%5Climits_%7Bx%20%5Cto-2%7D%20%28x%2B%202%29%5E2%20q%28x%29%20%3D%20%20%5Clim%20%5Climits_%7Bx%20%5Cto2%7D%20%28x%2B%202%29%5E2%20%5Cdfrac%7B7%7D%7B%28x%2B2%29%5E2%28x-2%29%5E2%7D)
![\implies \lim \limits_{x \to2} \dfrac{7}{(x-2)^2}](https://tex.z-dn.net/?f=%5Cimplies%20%20%5Clim%20%5Climits_%7Bx%20%5Cto2%7D%20%20%5Cdfrac%7B7%7D%7B%28x-2%29%5E2%7D)
![\implies \dfrac{7}{16}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B7%7D%7B16%7D)
Hence, one (1) of them is non-analytical at x = 2.
Thus, x = 2 is an irregular singular point.
Answer:
$67.60
Step-by-step explanation:
Paint can only be purchased in 1-quart, 1-gallon, and 5-gallon containers. How much will all supplies for the project cost if the cans of paint cost $10.90 for a quart, $34.90 for a gallon, and $165.00 for 5 gallons?
Answer: ![-4,-15;\ \left(-\dfrac{19}{2},-\dfrac{121}{4}\right)](https://tex.z-dn.net/?f=-4%2C-15%3B%5C%20%5Cleft%28-%5Cdfrac%7B19%7D%7B2%7D%2C-%5Cdfrac%7B121%7D%7B4%7D%5Cright%29)
Step-by-step explanation:
Given
Function is ![F(t)=t^2+19+60](https://tex.z-dn.net/?f=F%28t%29%3Dt%5E2%2B19%2B60)
Zeroes of the function are
![t^2+19t+60=0\\\\\Rightarrow t=\dfrac{-19\pm\sqrt{19^2-4\times 1\times 60}}{2\times 1}\\\\\Rightarrow t=\dfrac{-19\pm \sqrt{121}}{2}\\\\\Rightarrow t=\dfrac{-19\pm 11}{2}\\\\\Rightarrow t=-4,-15](https://tex.z-dn.net/?f=t%5E2%2B19t%2B60%3D0%5C%5C%5C%5C%5CRightarrow%20t%3D%5Cdfrac%7B-19%5Cpm%5Csqrt%7B19%5E2-4%5Ctimes%201%5Ctimes%2060%7D%7D%7B2%5Ctimes%201%7D%5C%5C%5C%5C%5CRightarrow%20t%3D%5Cdfrac%7B-19%5Cpm%20%5Csqrt%7B121%7D%7D%7B2%7D%5C%5C%5C%5C%5CRightarrow%20t%3D%5Cdfrac%7B-19%5Cpm%2011%7D%7B2%7D%5C%5C%5C%5C%5CRightarrow%20t%3D-4%2C-15)
Using completing the square method
![y=t^2+2\times \dfrac{19}{2}t+\dfrac{19^2}{2^2}-\dfrac{19^2}{2^2}+60\\\\y=\left(t+\dfrac{19}{2}\right)^2+60-\dfrac{361}{4}\\\\y=\left(t+\dfrac{19}{2}\right)^2-\dfrac{121}{4}\\\\y+\dfrac{121}{4}=\left(t+\dfrac{19}{2}\right)^2\\\\\left(y-(-\dfrac{121}{4}\right)=\left(t-(-\dfrac{19}{2})\right)^2\\\\\text{The vertex is }\left(-\dfrac{19}{2},-\dfrac{121}{4}\right)](https://tex.z-dn.net/?f=y%3Dt%5E2%2B2%5Ctimes%20%5Cdfrac%7B19%7D%7B2%7Dt%2B%5Cdfrac%7B19%5E2%7D%7B2%5E2%7D-%5Cdfrac%7B19%5E2%7D%7B2%5E2%7D%2B60%5C%5C%5C%5Cy%3D%5Cleft%28t%2B%5Cdfrac%7B19%7D%7B2%7D%5Cright%29%5E2%2B60-%5Cdfrac%7B361%7D%7B4%7D%5C%5C%5C%5Cy%3D%5Cleft%28t%2B%5Cdfrac%7B19%7D%7B2%7D%5Cright%29%5E2-%5Cdfrac%7B121%7D%7B4%7D%5C%5C%5C%5Cy%2B%5Cdfrac%7B121%7D%7B4%7D%3D%5Cleft%28t%2B%5Cdfrac%7B19%7D%7B2%7D%5Cright%29%5E2%5C%5C%5C%5C%5Cleft%28y-%28-%5Cdfrac%7B121%7D%7B4%7D%5Cright%29%3D%5Cleft%28t-%28-%5Cdfrac%7B19%7D%7B2%7D%29%5Cright%29%5E2%5C%5C%5C%5C%5Ctext%7BThe%20vertex%20is%20%7D%5Cleft%28-%5Cdfrac%7B19%7D%7B2%7D%2C-%5Cdfrac%7B121%7D%7B4%7D%5Cright%29)
Step-by-step explanation:
ED = EB
2x +3 = 5x -15
3+15=5x -2x
18 = 3x
18 ÷ 3 = x
x = 6